Aldosterone Acting through the CNS Sensitizes Angiotensin II -Induced Hypertension - Xue, Baojian (2012)
Previous studies have shown that preconditioning rats with a non-pressor dose of angiotensin II (AngII) sensitizes the pressor response produced by later treatment with a higher dose of AngII and that AngII and aldosterone (Aldo) can modulate each other’s pressor effects through actions involving the central nervous system (CNS). The current studies tested whether Aldo can cross-sensitize the pressor actions of AngII to enhance hypertension by employing an Induction-Delay-Expression (I-D-E) experimental design. Male rats were implanted for telemetered BP recording. During I, sub-pressor doses of either sc or icv Aldo were delivered for 1 week. Rats were then rested for 1 week (D) to assure that any exogenous Aldo was metabolized. After this, AngII was given sc for 2 weeks (E). During I and D Aldo had no sustained effect on BP. However, during E AngII-induced hypertension was greater in the groups receiving sc or icv Aldo during I in comparison to those groups receiving vehicle. Central administration of mineralocorticoid receptor antagonist blocked sensitization. Brain tissue collected at the end of D and E showed increased mRNA expression of several renin-angiotensin-aldosterone system components in cardiovascular-related forebrain regions of cross-sensitized rats. Cultured subfornical organ neurons preincubated with Aldo displayed greater increases in [Ca(2+)](i) after AngII, and there was greater Fra-like immunoreactivity present at the end of E in cardiovascular-related forebrain structures. Taken together, these results indicate that Aldo pretreatment cross-sensitizes the development of AngII-induced hypertension probably by mechanisms that involve the CNS.